2015
DOI: 10.1007/s00277-014-2279-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of porcine antihuman lymphocyte immunoglobulin compared to rabbit antithymocyte immunoglobulin as a first-line treatment against acquired severe aplastic anemia

Abstract: Immunosuppressive therapy (IST) with antithymocyte immunoglobulin (ATG) or antilymphocyte immunoglobulin (ALG) and cyclosporine A (CsA) is the treatment of choice against severe aplastic anemia (SAA) worldwide. However, a comparison of the efficacy of porcine ALG (pALG) and rabbit ATG (rATG) as a first-line treatment for acquired SAA has not been reported. In the present study, we retrospectively analyzed SAA patients treated with either pALG (n = 43) or rATG (n = 32) and compared their hematologic responses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In a study by Liu et al . , the 1‐yr response rate was 69.05% in the pALG group, which was not significantly different compared with the rATG group. In the present study, the 1‐yr response rate in the pALG group was substantially higher, which could be associated with the younger age, lower VSAA percentage, and longer time from diagnosis to treatment.…”
Section: Discussionmentioning
confidence: 71%
“…In a study by Liu et al . , the 1‐yr response rate was 69.05% in the pALG group, which was not significantly different compared with the rATG group. In the present study, the 1‐yr response rate in the pALG group was substantially higher, which could be associated with the younger age, lower VSAA percentage, and longer time from diagnosis to treatment.…”
Section: Discussionmentioning
confidence: 71%
“…Porcine ALG is a product developed in China and was approved by the Sino Food and Drug Administration in 2004. A series of retrospective studies evaluating the efficacy of P-ALG in treatment of AA were conducted [ 8 13 , 21 24 ]. P-ALG was reported to have similar or superior overall response at 6 months compared to R-ATG (64.0–79.4% vs 48.1–64.7%) in the IST treatment for AA patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…P-ALG was reported to have similar or superior overall response at 6 months compared to R-ATG (64.0–79.4% vs 48.1–64.7%) in the IST treatment for AA patients [ 25 ]. Liu et al [ 21 ] retrospectively analyzed SAA patients treated with either P-ALG (n = 43) or R-ATG (n = 32) plus CSA, and suggested there were no significant difference in 2-year OS between the 2 groups (87.4% ± 6.2% vs 83.2% ± 7.8%, P = 0.493). Other studies [ 10 , 11 ] comparing the efficacy of P-ALG and R-ATG in the IST treatment showed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were treated in sterile rooms with strict reverse isolation from the beginning of therapy. The patients in the IST group were treated with rabbit ATG (rATG) 3.75 mg/kg/day or porcine antihuman lymphocyte immunoglobulin (pALG) 30 mg/kg/day from day 1 to day 5 ( 28 ). Oral CsA treatment (3–5 mg/kg/day) was started on the first day of rATG/pALG, and was administered for at least 2 years (with dose adjustments to achieve a whole-blood trough level of 200–250 ng/ml for adults and 150–200 ng/ml for children).…”
Section: Methodsmentioning
confidence: 99%